Health risk assessment of exposure to the Middle-Eastern Dust storms in the Iranian megacity of Kermanshah. - Goudarzi, G.; Daryanoosh, S. M.; Godini, H.; Hopke, P. K.; Sicard, P.; De Marco, A.; Rad, H. D.; Harbizadeh, A.; Jahedi, F.; Mohammadi, M. J.; Savari, J.; Sadeghi, S.; et al. (Public Health (Elsevier), 2017)
Objective: This study assessed the effects of particulate matter (PM), equal or less than 10 μm in aerodynamic diameter (PM10), from the Middle-Eastern Dust events on public health in the megacity of Kermanshah (Iran). Study design: This study used epidemiological modeling and monitored ambient air quality data to estimate the potential PM10 impacts on public health. Methods: The AirQ2.2.3 model was used to calculate mortality and morbidity attributed to PM10 as representative of dust events. Using Visual Basic for Applications, the programming language of Excel software, hourly PM10 concentrations obtained from the local agency were processed to prepare input files for the AirQ2.2.3 model. Results: Using baseline incidence, defined by the World Health Organization, the number of estimated excess cases for respiratory mortality, hospital admissions for chronic obstructive pulmonary disease, for respiratory diseases, and for cardiovascular diseases were 37, 39, 476, and 184 persons, respectively, from 21st March, 2014 to 20th March, 2015. Furthermore, 92% of mortality and morbidity cases occurred in days with PM10 concentrations lower than 150 μg/m3. The highest percentage of person-days occurred for daily concentrations range of 100–109 μg/m3, causing the maximum health end-points among the citizens of Kermanshah. Conclusions: Calculating the number of cumulative excess cases for mortality or morbidity attributed to PM10 provides a good tool for decision and policy-makers in the field of health care to compensate their shortcomings particularly at hospital and healthcare centers for combating dust storms. To diminish these effects, several immediate actions should be managed in the governmental scale to control dust such as spreading mulch and planting new species that are compatible to arid area.